Transcending subjects : Augustine, Hegel and theology - Holsclaw, Geoff (Chichester : Wiley-Blackwell, 2016)
Transcending Subjects: Augustine, Hegel and Theology engages the seminal figures of Hegel and Augustine around the theme of subjectivity, with consideration toward the theology and politics of freedom.
Includes bibliographical references and index.
Print version record.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Augustine, -- Saint, Bishop of Hippo; Augustine, -- Saint, Bishop of Hippo; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Transcendence (Philosophy); PHILOSOPHY / Essays; PHILOSOPHY / Reference; PHILOSOPHY / Movements / Idealism; Transcendence (Philosophy); Electronic books